Justicia carnea extracts ameliorated hepatocellular damage in streptozotocin-induced type 1 diabetic male rats via decrease in oxidative stress, inflammation and increasing other risk markers. (17th February 2023) - Falode, John Adeolu; Ajayi, Oluwaseun Igbekele; Isinkaye, Tolulope Victoria; Adeoye, Akinwunmi Oluwaseun; Ajiboye, Basiru Olaitan; Brai, Bartholomew I. C.
Abstract: Introduction Diabetes mellitus is still a raging disease not fully subdued globally, especially in Africa. Our study aims to evaluate the anti-diabetic potentials of Justicia carnea extracts [crude (JCC), free (JFP) and bound phenol (JBP) fractions], in streptozotocin (STZ)-induced type-1 diabetes in male albino rats. Materials and Methods About thirty (30) animals were induced for type 1 diabetes with STZ; thereafter, treatment began for 14 days, after which the animals were euthanized, blood/serum was collected, the liver was removed and divided into two portions, for biochemical and histopathological analyses. Standard procedures were used to evaluate the liver biomarkers, like alanine transaminase (ALT), fructose-1, 6-bisphosphatase, glucose-6- phosphatase, hexokinase activities, albumin, bilirubin, hepatic glucose concentrations; antioxidant status and pro- and anti-inflammatory cytokines were similarly assessed. Results These results revealed that the extracts ameliorated the harmful effects of STZ-induced diabetes in the liver by enhancing the activities of liver-based biomarkers, reducing the concentrations of pro-inflammatory cytokines and increasing the anti-inflammatory cytokine. Discussion The results agreed with previous research, and the free phenol fraction showed excellent results compared to others Conclusion These suggested that J. carnea could serve as an alternative remedy in ameliorating liver complications linked to oxidative damage and inflammation in STZ-induced type-1 diabetes.